Global trends in nature’s contributions to people - Brauman, Kate A.; Garibaldi, Lucas A.; Polasky, Stephen; Aumeeruddy-Thomas, Yildiz; Brancalion, Pedro H.S.; DeClerck, Fabrice A.J.; Jacob, Ute; Mastrángelo, Matias Enrique; Nkongolo, Nsalambi V.; Palang, Hannes; Pérez Méndez, Néstor; Shannon, Lynne J.; et al. (National Academy of Sciences, 2020)
Understanding and tracking nature’s contributions to people provides critical feedback that can improve our ability to manage earth systems effectively, equitably, and sustainably. Declines in biodiversity and ecosystem functions over the past 50 y have decreased the ability of nature to contribute to quality of life. Changes in technology and adaptation in social systems has partially offset the negative impacts of environmental change on quality of life, but downward trends have still occurred for many categories of nature’s contributions.